PENGGUNAAN METODE TANYA JAWAB BERBASIS MEDIA WHATSAPP DALAM MATA PELAJARAN PAI DI MASA PANDEMI COVID 19 DI SDN 01 TELAJUNG BEKASI - Farhah Azizah Azizah; Masykur Mansyur; Abdul Kosim (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
The implementation of online learning in the midst of this pandemic is expected so that the learning process will still run smoothly even though it is only carried out online and so that learning can still run smoothly and effectively. In this study, the implementation of online learning was carried out using whatsapp media. Whatsapp is a messaging and miscellaneous app for smartphones. In addition to sending WhatsApp messages, they are interrelated so that they will produce optimal learning activities. The method has a very high place in an effort to achieve goals, because it is a means of delivering subject matter arranged in the curriculum. Teachers are required to be able to choose and apply appropriate learning methods to assist teachers in delivering materials in order to improve student achievement in the teaching and learning process. This research took place at SDN 01 Telajung Bekasi using qualitative descriptive research. The use of the question and answer method properly and appropriately, will be able to stimulate students' interest and motivation in learning. the teacher asks them questions and they respond in the whatsapp group. Through the question and answer method it will stimulate students' thinking and responses so as to arouse student activity in distance learning by answering the author's questions or asking the author.